El perfil de los usuarios de Twitter más influyentes en Ecuador y la influencia del mensaje en la captación de seguidores (2016)
The diffusion of Internet as a contemporary public space has determined the emergence of new social participatory practices, which might undermine the paradigms of the information society. The goal of this paper is to describe the profile of the TOP Twitter users in Ecuador and examine whether the tone of the message and frequency of use determine the winning/losing of followers. We content analyzed the 100 Twitter users with most followers in Ecuador during 2014 and repeated the same measurement in 2015. The findings show that the users' profiles are extremely localized and public. Additionally, data did not show enough evidence to support the hypotheses that the features of the message influence the number of followers, which suggested the creation of Twitter local dynamics in Ecuador when compared to other countries of the region.